NUSYÛZ ISTERI DAN SUAMI DALAM AL-QURẦN (Sebuah Pendekatan Tematis) - Erman Erman (Marwah: Jurnal Perempuan, Agama dan Jender, 2010)
This article discusses regarding nusyuz of wife and husband in al-Quran perspective. The discussing is focused on the meaning of nusyuz, kinds of nusyuz, and solution which can apply to solve it. According to al-Quran, there are three steps that can be used by husband if his wife nusyûz. They are giving advice to wife, aparting bed room, and blowing. Vice versa, when the husband nusyuz, al-Qur'an gives reference to perform the agreement of peace. When the agreement of peace which offered by the wife is not fulfilled by the husband, then she does not ridha, she can do khulû' or divorce where the wife gives ransom so that her husband divorce her.